Rola rodziny w rozwoju dziecka - Żytka-Rydosz, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
W artykule podjęto próbę ukazania roli rodziny w rozwoju dziecka. Jest ona najważniejszym środowiskiem z perspektywy kształtowania osobowości. Rodzice pełnią rolę nauczycieli, których zachowania zapisują się trwale w umyśle dziecka. Będzie ono z określonych wzorów czerpać przez całe życie. Kluczowe jest zapewnienie dziecku poczucia bezpieczeństwa, dzięki czemu jego rozwój będzie przebiegał prawidłowo. Istnieje wiele definicji pojęcia „rodzina”, co wskazuje na jej wieloaspektowość w optyce wielu dyscyplin naukowych. Niewątpliwie w rodzinie dziecko zaspokaja różnorodne swoje potrzeby, np. emocjonalne, społeczne. Potrzeby biologiczne, które były na pierwszym miejscu są wpisane w dobrobyt współczesnego społeczeństwa. Czerpie ze wszystkiego, co dają mu bliscy. Rodzinie przypisuje się także wiele ról, funkcji i zadań. Jest to przede wszystkim środowisko narodzin, rozwoju i wychowania człowieka. Kontekstem dla rozważań stała się rodzina dysfunkcyjna. To w niej należy upatrywać zagrożeń dla prawidłowego rozwoju i funkcjonowania dziecka. Zwrócono uwagę zarówno na cechy rodziny prawidłowej, jak i na cechy rodziny dysfunkcyjnej. W pierwszej dziecko wychowywane jest w poczuciu bezpieczeństwa i miłości ze strony rodziców i całej rodziny. W drugim musi dostosować się do problemów rodziny, które stoją na piedestale, wykształcić cechy, które zapewnią mu przetrwanie. W rodzinie dysfunkcyjnej potrzeby dzieci nie są na pierwszym miejscu, nie są spełniane w odpowiednim stopniu. Powodem deprywacji potrzeb są dysfunkcje, np. uzależnienie członków rodziny od alkoholu, narkotyków bądź też stosowanie przemocy. Występowanie trudnych zjawisk wpływa znacząco na pozycję dziecka. Rodzina nie jest w stanie urzeczywistnić przypisywanych jej ról, zadań i funkcji z uwagi na występujące w niej zaburzenia. W związku z tym, wychowanie w rodzinie prawidłowej i nieprawidłowej (dysfunkcyjnej) posiada swoje konsekwencje w przyszłości, kiedy dziecko staje się dorosłym człowiekiem.

In the article the attempt has been undertaken to present the role of the family in a child’s development. The family is the most important environment as far as the perspective of personality’s development is concerned. The parents function as teachers whose behaviours are permanently recorded in their children’s minds. This way the specific patterns of behaviour, which the child is going to use even throughout their entire life, are created. It is of the key importance to provide each child with the sense of security as it guarantees their proper development. The term ‘family’ can be defined in a lot of various ways, which indicates its multifacetedness in the optics of multiple branches of science. Undoubtedly, the family is where a child satisfies their various needs, for example emotional or social ones. Children draw on everything that their closest relatives offer them. There are a lot of roles, functions and tasks that are ascribed to the family, but first of all it is the environment of each individual human being’s birth, growth, development, education and upbringing. The primary context of the deliberations this article is based on is the dysfunctional family, which is the main source of dangers for each child’s proper functioning and development. The author of the article has paid attention to the set of features that characterise both correctly and incorrectly functioning families. In the first one of previously mentioned the child is brought up surrounded by the sense of security and the feeling of love which derive not only from the parents but all the family members, too. On the other side, the children who are brought up in dysfunctional families have to adapt their everyday life to their families’ problems, which are of the primary importance, and this way they are forced to develop such features of their characters which will enable them to survive. In dysfunctional families the children’s needs are not the most important ones and that is why they are not satisfied to an adequate level. The main reasons for the depravity of children’s needs are the co-existing dysfunctions such as: parents’ alcohol abuse, drug addiction and using violence. The existence of these extremely difficult phenomena influences the child’s position in a significant way. Such families are unable to perform the traditional roles, tasks and functions that are ascribed to them, because of the disorders in their existence. All these lead to a conclusion that having been brought up in a proper or improper (dysfunctional) family has its strong consequences for a child’s future and deeply influences their functioning as a grown-up person.
The role of the family in child development
Keywords: rola rodziny; rozwój dziecka; rodzina dysfunkcyjna; kształtowanie osobowości dziecka; the role of the family; a child’s development; a dysfunctional family; the creation of the child’s personality